Do CEOs influence CFOs’ equity incentives to manage earnings? - Ruonan Liu (STIE Malangkucecwara, 2022)
This study examines whether CEOs’ incremental equity incentives relative to CFOs (i.e., the gap between CEO equity incentives and CFO equity incentives) and CEO power constrain or exacerbate CFOs' equity incentives to manage earnings. In most companies, CEOs own more equity than CFOs and may pressure CFOs to engage in earnings management. I find no evidence that CEO incremental equity incentives or CEO power affect the association between CFOs’ equity incentives and earnings management. In addition, I find that CFOs’ equity incentives mitigate real earnings management activities, which can help align the interests of CFOs with shareholders.